الشعر العربي في بلاد يوربا : عيسى ألبي أبو بكر نموذجا : دراسة فنية تحليلية - صارمي، عبد القهار عبد الوهاب (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This research studies Arabic Poetry of Yoruba land, southwestern Nigeria, taking Doctor Isa Alabi Abu-Bakr as an archetype representative of the Yoruba on the modern Arabic poetic scene. The originality and quality of his lyrics justifies his choice. Thus, a duo of his anthologies, al-Riyad and al-Suba'iyyat were designated as the laboratory for the study. This research, while utilizing historical, descriptive and inductive approaches is essentially analytical, and attempts to unlock the door to the literary, artistic and aesthetic treasures of his lyrics. The study opens with a re-survey of history of the Yoruba, thereby retracing the contact of Islam with the sub-region, and the eventual introduction of Arabic language and literature thereto. A lighthouse was built wherefrom we cast light on the prominent poets of the province and their poetics, all as a prelude to discussion on our subject matter, Isa Alabi Abu-Bakr. After citing his biography and highlighting his literary outputs, we subjected the content and structure of his lyrics to a critical artistic analysis. The study however mirrored the fact that the Yoruba have a remarkable poetic faculty, and that Isa Alabi Abu-Bakr is distinct amongst a handful of the Yoruba Arabic poets, who ably represents modern Arabic lyricism in the Yoruba sub-region. It is therefore, not hyperbolic, to assert that Abu-Bakr, among other non-Arab poets, is one whose poetry is found on the race course alongside works of original Arab poets. Hence, considering the stylistic quality and thematic quantity of the Yoruba Arabic poetry, we strongly recommend that Arabic lyrics of other Yoruba poets be studied from literary and artistic perspectives. Other researchers may still examine Abu-Bakr's poetics from panoramas contrastive to the views expressed in this study. Still, others may engage in a comparative study of poetics of non-Arabs between the ancient and the modern times.